2017
DOI: 10.1186/s13047-017-0230-5
|View full text |Cite
|
Sign up to set email alerts
|

Defining the gap: a systematic review of the difference in rates of diabetes‐related foot complications in Aboriginal and Torres Strait Islander Australians and non‐Indigenous Australians

Abstract: BackgroundThe Aboriginal and Torres Strait Islander community has an increased risk of developing chronic illnesses including diabetes. Among people with diabetes, foot complications are common and make a significant contribution to the morbidity and mortality associated with this disease. The aim of this review was to systematically evaluate the literature comparing the rates of diabetes related foot complications in Aboriginal and Torres Strait Islander Australians to non-Indigenous Australians.MethodsMEDLIN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
68
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(77 citation statements)
references
References 46 publications
7
68
2
Order By: Relevance
“…Interestingly, we found no marked differences between Indigenous and non-Indigenous people for these risk factors, in contrast to a previous systematic review [ 40 ]. This may be explained by our tighter inclusion criteria that included only population-based publications and in turn only identified studies from urban settings [ 32 ], while the previous review predominantly identified single site clinic-based studies from remote settings [ 40 ], with geographical remoteness known to increase DFD rates [ 41 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Interestingly, we found no marked differences between Indigenous and non-Indigenous people for these risk factors, in contrast to a previous systematic review [ 40 ]. This may be explained by our tighter inclusion criteria that included only population-based publications and in turn only identified studies from urban settings [ 32 ], while the previous review predominantly identified single site clinic-based studies from remote settings [ 40 ], with geographical remoteness known to increase DFD rates [ 41 ].…”
Section: Discussioncontrasting
confidence: 99%
“…We also found differences in amputation rates within different sub-populations of Australia. Interestingly, we found up to 38 fold higher rates for amputations in Indigenous populations compared to the non-Indigenous population [ 23 ], and much higher than the 3–6 fold higher rates for amputations in Indigenous populations reported in the previously discussed systematic review [ 40 ]. Perhaps implicated in this finding, was that we also found geographical variation in amputation rates in two nation-wide publications [ 20 , 31 ].…”
Section: Discussionmentioning
confidence: 82%
“…Best estimates show that about 50 000 Australians have DFD (ulcers, infections and ischaemia) and 300 000 have major risk factors (peripheral neuropathy and peripheral arterial disease) for developing DFD 4 . Indigenous Australians are disproportionally affected, with a 3–6‐fold increased likelihood of developing DFD 8 …”
Section: The Problemmentioning
confidence: 99%
“…4 Indigenous Australians are disproportionally affected, with a 3e6fold increased likelihood of developing DFD. 8 DFD is a complex condition that is not easily identified, prevented or treated. 1,9 It commonly develops from trauma in the presence of peripheral neuropathy or peripheral arterial disease and is complicated by infection.…”
mentioning
confidence: 99%
“…9 Additionally, Aboriginal and Torres Strait Islander peoples have a 3-6 times greater risk of diabetic foot ulcer than the non-Indigenous population. [9][10][11] Australian data provide indirect evidence that strategies to improve community-and hospital-based foot care for patients with type 2 diabetes are beneficial. 9 In this month's issue of Australian Journal of General Practice, Reardon and colleagues explore the multidisciplinary approach focusing on frequent assessment, early recognition and management of diabetic foot as the central focus in reducing the associated morbidity and mortality.…”
mentioning
confidence: 99%